Brief quiet ego contemplation reduces oxidative stress and mind-wandering - Wayment, Heidi A.; Collier, Ann F.; Birkett, Melissa; Traustadóttir, Tinna; Till, Robert E. (Frontiers in Psychology, 2015)
Excessive self-concern increases perceptions of threat and defensiveness. In contrast, fostering a more inclusive and expanded sense of self can reduce stress and improve well-being. We developed and tested a novel brief intervention designed to strengthen a student’s compassionate self-identity, an identity that values balance and growth by reminding them of four quiet ego characteristics: detached awareness, inclusive identity, perspective taking, and growth. Students (N = 32) in their first semester of college who reported greater self-protective (e.g., defensive) goals in the first two weeks of the semester were invited to participate in the study. Volunteers were randomly assigned to one of three conditions: quiet ego contemplation (QEC), QEC with virtual reality headset (QEC-VR), and control. Participants came to the lab three times to engage in a 15-minute exercise in a 30-day period. The 15-minute Quiet Ego Contemplation (QEC) briefly described each quiet ego characteristic followed by a few minutes time to reflect on what that characteristic meant to them. Those in the QEC condition reported improved quiet ego characteristics and pluralistic thinking, decreases in a urinary marker of oxidative stress, and reduced mind-wandering on a cognitive task. Contrary to expectation, participants who wore the VR headsets while listening to the QEC demonstrated the least improvement. Results suggest that a brief intervention that reduces self-focus and strengthens a more compassionate self-view may offer an additional resource that individuals can use in their everyday lives.